ESG IMPACTS ON COST OF CAPITAL: EMPIRICAL EVIDENCE FROM LISTED COMPANIES ON THE STOCK EXCHANGE OF THAILAND - SUMRANSAT, Thitiporn; เห็นสว่าง สุรางค์; พงศ์สุพัฒน์ อภิชาติ; เลาหวิเชียร ทิพย์รัตน์ (Thai Interdisciplinary and Sustainability Review, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) factors on the cost of capital for listed companies on the Stock Exchange of Thailand, considering both aggregate ESG scores and disaggregated scores across dimensions. It also analyzes financial performance, firm characteristics, and macroeconomic factors. The findings indicate that the aggregate ESG score, debt-to-total assets ratio, sales growth, firm age, firm size, and Gross Domestic Product (GDP) are significantly and negatively associated with the weighted average cost of capital. Furthermore, only the Environmental score shows a significant negative effect on all measures of the cost of capital. These results highlight the important role of ESG in promoting corporate sustainability and reducing the cost of capital, ultimately contributing to the long-term value of firms.